Clinical Aspects of Prevention and Management of Primary Inferior Oblique Muscle Overaction - I. L. Plisov; V. B. Pushchina; N. G. Antsiferova; G. V. Gladysheva; D. R. Mamulat; M. A. Sharokhin; K. A. Belousova (Acta Biomedica Scientifica, 2019)
Background. Primary inferior oblique muscle overaction (PIOOA) may occur for various reasons and happens to 72 % patients with infantile esotropia. The criterion for the first surgical step is prevalence of vertical or horizontal deviation. The choice of tactics weakening inferior oblique muscle is ambiguous.Aims: to carry out retrospective analysis of PIOOA frequency in patients with infantile esotropia; to assess influence of esodeviation reduction by a surgical, chemodenervational or prismatic method on the existing PIOOA dynamics; to assess clinical and functional results of PIOOA treatment.Methods and methods. The retrospective analysis of 572 patients’ cases lay in assessment of PIOOA frequency and rate in patients with infantile esotropia that manifested under 9 months, with different treatment tactics. The prospective part of the research included two groups of patients. Group 1 (106 patients, 222 eyes) – studying the influence of surgical treatment of PIOOA. Group 2 (127 patients, 207 eyes) – studying the effectiveness of surgical PIOOA treatment. Conclusion. PIOOA frequency in case of different treatment tactics for patients with infantile esotropia is from 17 to 69 %, and the degree of its clinical manifestation is from 1.2 ± 0.4 to 2.6 ± 0.8. Bilateral weakening of medial rectus muscle reduces its probability up to 17–19 %, and the degree of its manifestation up to 1.2 ± 0.4. In cases of combination of PIOOA with infantile esotropia from 20 to 25° with paretic component, it is reasonable to carry out esodeviation reduction by means of bilateral recession, chemorecession or prismatic correction as the first treatment stage, whereas the rate of existing PIOOA is credibly reduced. In cases of choice of tactics, which is necessary for clinically significant reduction or elimination of PIOOA, it is reasonable to carry out chemorecession, marginal partial myotomy or myectomy depending on the PIOOA manifestation.